Investigating the Influences of Self Esteem on Student’s Academic Performance in English Language: A Case Study of Secondary Schools in Rubanda. - Ahurira, Divotter (Kabale University, 2024)
The study examined the impact of self-esteem on students' academic performance in the English language among secondary school students. The objectives were to explore how self-esteem influences students' performance in English and to assess the prevalence of low self-esteem among secondary schools in Rubanda District. A descriptive research design was employed, with data collected through questionnaires and interviews. Regarding the impact of self-esteem on English language learning, the majority of respondents indicated that self-esteem enhances students' problem-solving abilities, enabling them to make sound judgments based on evidence and criteria. Fewer respondents noted that self-esteem contributes to students' personal development and individual characteristics. Among the challenges faced by students with low self-esteem in English language learning, the most common issue identified was a lack of basic communication skills, which hinders students' progress in mastering these skills. The least mentioned challenge was feelings of inferiority among students from disadvantaged backgrounds, which prevented them from actively participating in learning activities. For solutions to these challenges, the majority of respondents emphasized the importance of providing a supportive and conducive learning environment to foster positive attitudes and higher motivation toward English language learning. A smaller number of respondents suggested that encouraging students to actively participate in the learning process would help them achieve their goals. The study recommended fostering motivation among both students and teachers to encourage active learning and engagement in communication skills development.